2022
DOI: 10.1097/hcr.0000000000000752
|View full text |Cite
|
Sign up to set email alerts
|

Built Environments and Cardiovascular Health

Abstract: Purpose: This review presents a general overview of the state of evidence on the relationships between neighborhood built environments and cardiovascular health outcomes among adults. We also summarize relevant literature on the associations of built environments with active living behaviors (physical activity [PA] and sedentary behavior), as they are considered as key behavioral pathways. Review Methods: We identified recently published systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Some previous studies that showed 40 lower hospitalization rates for cardiovascular disease, 41 as well as lower risk of incidence of cardiovascular disease, 42 did not include air pollution or walkability exposures. Chandrabose et al 21 proposed that more walkable neighborhoods have destinations to which some people still drive, creating vehicle emissions that adversely affect health. We found that higher walkability was associated with lower diabetes prevalence only in areas with lower levels of PM 2.5 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some previous studies that showed 40 lower hospitalization rates for cardiovascular disease, 41 as well as lower risk of incidence of cardiovascular disease, 42 did not include air pollution or walkability exposures. Chandrabose et al 21 proposed that more walkable neighborhoods have destinations to which some people still drive, creating vehicle emissions that adversely affect health. We found that higher walkability was associated with lower diabetes prevalence only in areas with lower levels of PM 2.5 .…”
Section: Discussionmentioning
confidence: 99%
“…Further analyses were run for PM 2.5 controlling for covariates and NO 2 , and vice versa. Potential interactions between walkability and air pollutants, proposed by a recent study, 21 were examined in relation to disease prevalence, with effects scaled to one unit of each exposure.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations